Sagot :
Solve by Factoring
- To solve the given, we must factor the left side of the equation. Then set factors equal to 0 in order to determine the final answer.
[tex] \\ \tt = {x}^{2} – 3x - 10 = 0 \\ = \tt(x+2)(x−5)=0 \\ = \tt \: x+2=0 \: or \: x−5=0 \\ = \tt\begin{gathered} \boxed{ \large \boxed{\tt{x=−2 \: , \: x=5}}} \end{gathered} \\ \\ [/tex]
Hope this helps! ❤
Equation Given:-
[tex] \red{ \boxed{ \sf{x}^{2} - 3x - 10 = 0}}[/tex]
[tex] \\ [/tex]
Step-by-step explanation:-
[tex] \\ [/tex]
[tex] \dashrightarrow \sf{x}^{2} - 3x - 10 = 0[/tex]
[tex] \\ [/tex]
[tex] \dashrightarrow \sf{x}^{2} - 5x + 2x - 10 = 0[/tex]
[tex] \\ [/tex]
(Splitting the middle term)
[tex] \\ [/tex]
[tex] \dashrightarrow \sf \{{x}^{2} - 5x \} + \{2x - 10 \} = 0[/tex]
[tex] \\ [/tex]
[tex] \dashrightarrow \sf x\{{x} - 5 \} + 2\{x - 5\} = 0[/tex]
[tex] \\ [/tex]
[tex] \dashrightarrow \sf \{x + 2 \} \{x - 5 \} = 0[/tex]
[tex] \\ [/tex]
Comparing:
[tex] \\ [/tex]
Value of x :-
x + 2 = 0
x = -2
Or
x - 5 = 0
x = 5
#CarryOnLearning